METHOF FOR DECONTAMINATION OF RADIOACTIVE MATERIALS (2000)
The invention relates to the method for decontamination of radioactive materials. The method for radioactive decontamination of material includes contacting material subject decontamination with diluted solution containing carbonate. This process is carried out in the presence of ion-exchange particles contained chelate forming functional groups or connected with them. In the following the ion-exchange particle separation from the diluted solution containing carbonate is carried out. Изобретение относится к способу дезактивации радиоактивных материалов. Способ дезактивации радиоактивных материалов включает контактирование материала, подлежащего дезактивации, с разбавленным раствором, содержащим карбонат. Этот процесс проводят в присутствии ионообменных частиц, которые либо содержат хелатинообразующие функциональные группы, либо связаны с ними. В последующем происходит отделение ионообменных частиц из разбавленного раствора, содержащего карбонат. Винахід відноситься до способу дезактивації радіоактивних матеріалів. Спосіб дезактивації радіоактивних матеріалів включає в себе контакт матеріалу, що підлягає дезактивації, з розбавленим розчином, що містить карбонат. Цей процес проводять у присутності іонообмінних частинок, які або містять хелатіноутворюючі функціональні групи, або пов'язані з ними. У подальшому відбувається відділення іонообмінних частинок з розбавленого розчину, що містить карбонат.